The Impact of Pkh Assistance on Poor Communities in Nunggi Village, Wera District, Bima Regency - Dodo Susanto (Business Management, 2025)
Poverty is one of the problems faced by every country. This is due to the poor condition of the country or its people who have limited skills to meet their needs. Several poverty alleviation policies have been decided and implemented by the Indonesian government, one of which is the Family Hope Program (PKH) which has existed since 2007. This study aims to analyze the forms of PKH assistance, the role of PKH companions and the impact of PKH on poor families in Nunggi Village, Wera District, Bima Regency. The results of the study show that (1) the forms of PKH assistance are PKH cash assistance and complementary assistance such as health insurance, education insurance, non-cash food assistance, Prosperous rice and other assistance from the regional government and the central government. (2) The role of PKH companions is to accompany PKH participants in verifying education and health, validating prospective PKH participants, updating data and family capacity building meeting activities. (3) the impact of PKH on poor families in Nunggi Village, Wera District, Bima Regency, namely, making people aware of living independently without depending on the government, being aware of education and health and caring about the environment. However, there are still people who claim to be poor to get assistance from the government even though their economic condition is quite capable or stable.